2010
DOI: 10.1073/pnas.0913602107
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model for TDP-43 proteinopathy

Abstract: Neuropathology involving TAR DNA binding protein-43 (TDP-43) has been identified in a wide spectrum of neurodegenerative diseases collectively named as TDP-43 proteinopathy, including amyotrophic lateral sclerosis (ALS) and frontotemporal lobar dementia (FTLD). To test whether increased expression of wide-type human TDP-43 (hTDP-43) may cause neurotoxicity in vivo, we generated transgenic flies expressing hTDP-43 in various neuronal subpopulations. Expression in the fly eyes of the full-length hTDP-43, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
229
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(252 citation statements)
references
References 33 publications
19
229
2
2
Order By: Relevance
“…Furthermore, the expression of a CTF in the fly eye fails to induce neurodegeneration 12 . This evidence indicates that the regulation of the total amount of full-length TDP-43, rather than that of the CTFs, is a critical determinant of cell survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the expression of a CTF in the fly eye fails to induce neurodegeneration 12 . This evidence indicates that the regulation of the total amount of full-length TDP-43, rather than that of the CTFs, is a critical determinant of cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The following primary antibodies were used: antiHaloTag polyclonal antibody (pAb; 1:500, G928A, Promega), anti-SNAP-tag pAb (1:1,000, P9310S, NEB), anti-GAPDH mAb (1:50,000, M171-3, MBL), anti-TARDBP pAb (1:2,500, 10782-2-AP, ProteinTech), anti-TARDBP pAb for C terminus region (1:500, NB110-55376, NOVUS Biologicals), anti-TDP-43 N terminus (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) To analyse the effect of each reagent, the cells were cultured in the presence of each reagent (caspase-4 inhibitor (50 mM), caspase-3/7 inhibitor (50 mM), NecroX-2 (20 mM), Necrostatin-1 (50 mM) and Dantrolene (30 mM)), and the medium that contained the reagent was replaced every 24 h (refs 15,40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because increased expression of TDP-43 is also toxic to motor neurons (12,13), it will be also important to identify a set of downstream targets of TDP-43 to facilitate our understanding of pathways that may be impacted by TDP-43. Interestingly, a recent RNAi knockdown study revealed histone deacetylase 6 (HDAC6) as a target of TDP-43 in cultured cells (14).…”
mentioning
confidence: 99%
“…In Drosophila, at least three different fly models elucidated the role of TBPH in neuronal and neuromuscular development. Indeed, flies mutants for TBPH closely reproduce most of the phenotypes observed in ALS patients like decreasing viability, affected synaptic transmission, defective locomotion and also age-related progressive neurodegeneration (Ritson et al 2010;Hazelett et al 2012;Li et al 2010;Neumann et al 2006). Recently, it has emerged that TBPH interacts with the Futsch protein, the Drosophila homolog to human MAP1B (Godena et al 2011) (Fig.…”
Section: Roles In Neuromuscular Developmentmentioning
confidence: 99%